Psychosocial Effects of COVID-19 in the Ecuadorian and Spanish Populations: A Cross-Cultural Study - Chocho-Orellana, Ángela Ximena; Samper-García, Paula; Malonda-Vidal, Elisabeth; Llorca-Mestre, Anna; Zarco-Alpuente, Alfredo; Mestre-Escrivá, Vicenta (Frontiers in Psychology, 2022)
Nowadays, we are overcoming one of the pandemics that has hit the world's population. The psychological and social effects of this pandemic are becoming more present. In this study, we present an analysis of the psychosocial effects of COVID-19 in two populations: first, a cross-sectional study in the Ecuadorian population (n = 301) and second, a comparative study with a subsample from the Spanish population (n = 83). Participants completed an online survey through the Limey Survey platform to: 1) describe how the Ecuadorian population felt (depression, anxiety and stress) before and after confinement; 2) analyze the effects that some emotional and behavioral variables (such as one's own prosocial tendencies, empathy and experiencing stress as a challenge or as a threat), considered all before confinement, have on depressive symptoms, anxiety and stress perceived after the confinement; 3) carry out a comparative study in a subsample of the Ecuadorian and Spanish samples. Results indicate that the Ecuadorian population generally experiences significantly more depressive symptoms, anxiety and stress after the confinement. On the other hand, results show that variables which predict depressive symptoms (R2 = 53.7%) and anxiety (R2 = 52.2%) after confinement are: greater public prosocial tendency, less stress understood as a challenge, and greater stress understood as a threat, as well as an empathic tendency that implies greater emotional regulation. Finally, experienced stress after confinement (R2 = 63%) was predicted by a greater public prosocial tendency, as well as an empathic tendency that implies greater emotional regulation. Regarding the last of the objectives, the results conclude that scores for depression, anxiety and stress are higher after confinement in both countries. However, there are differences in the variables which predict depressive symptoms, anxiety and stress. The results reveal, on the one hand, the similarity of the psychosocial effects that are being experienced, regardless of the country and, on the other, the differences in the variables that can help explain these effects. This can contribute to the constitution of intervention plans which aim to soften and alleviate the effects produced by a situation such as that experienced with COVID-19.